DEVELOPMENT OF BLENDED LEARNING-BASED PPKn TEACHING MATERIALS TO IMPROVE PGMI STUDENTS' LEARNING OUTCOMES IAIN PADANGSIDIMPUAN - Lubis, Maulana Arafat (PD PGMI se Indonesia, 2021)
This study aims to determine the effectiveness of PPKn teaching materials based on Blended Learning (BL). This study uses the RnD (Research and Development) method with the ADDIE development model. The population of this study was the fourth-semester students of the PGMI IAIN Padangsidimpuan Study Program. The sampling technique used in this study is purposive sampling, so the sample is 35 students. Data collection techniques using Google Form-assisted questionnaires, Kahoot-assisted learning outcomes tests, interviews, observations, and documentation. Analysis of research data using descriptive statistics assisted by STATCAL and EAVIS software. The research results show that PPKn-based teaching material design is excellent and has a good level of validation based on expert judgment. The level of effectiveness is also excellent, seen from student learning outcomes with the average value of PPKn MI/SD Low-Class courses on the pre-test is 64.7143; post-test I (meeting I) was 74.5714; post-test II (meeting I) was 79.5714; post-test II (meeting I) was 83; post-test II (meeting II) was 88.